2001
DOI: 10.1021/es010010f
|View full text |Cite
|
Sign up to set email alerts
|

Sorption and Desorption Behavior of Organotin Compounds in Sediment−Pore Water Systems

Abstract: Sediments contaminated with organotin compounds (OTs), in particular triorganotins (TOTs), are abundant in areas with high shipping activities. To assess the possible remobilization of these highly toxic compounds from such sediments, a profound understanding of their sorption/desorption behavior is necessary. In this work the extent and reversibility of sorption of OTs to sediments has been investigated using contaminated freshwater harbor sediments and two certified OT containing marine sediments. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 22 publications
9
52
1
3
Order By: Relevance
“…These results correspond also to the conclusions presented by e.g. Berg et al (2001), Burton et al (2004), Fent (1996 or Hoch and Schwesig (2004), who suggested that OTs are more likely to bind to fine particles associated with higher organic carbon content, as humic acids readily form complexes with OTs.…”
Section: Correlations Between Variablessupporting
confidence: 91%
“…These results correspond also to the conclusions presented by e.g. Berg et al (2001), Burton et al (2004), Fent (1996 or Hoch and Schwesig (2004), who suggested that OTs are more likely to bind to fine particles associated with higher organic carbon content, as humic acids readily form complexes with OTs.…”
Section: Correlations Between Variablessupporting
confidence: 91%
“…Fent found from studies in seawater that 95-99% of the total TBT is present in the dissolved phase 2 . Berg et al described the adsorption-desorption behavior of TBT in sediments as a fast and reversible process involving mainly particulate organic matter 26 . In TSB the low availability of particles of organic nature (0.13 to 1.3 mg L -1 ) is a factor that contributes to increasing residence time of these labile compounds in the water phase 25 .…”
Section: Resultsmentioning
confidence: 99%
“…The binding of organotin species to sediments has been demonstrated to be a reversible process involving particulate organic matter in the sediments and desorption occurs readily. As a consequence, disturbance of contaminated sediments is likely to result in an increase in organotin concentrations in the water column, although if undisturbed contaminated sediments are unlikely to be an input source (Berg et al, 2001). However, laboratory studies have indicated that sediment bound TBT may not be as available as new inputs and that the development of pollution induced community tolerance may result from long-term exposure to contaminated sediments (Dahllof et al, 2001).…”
Section: Resultsmentioning
confidence: 99%